A1.17 Analysis of two essential sub-processes of long distance migration of synovial fibroblasts from patients with rheumatoid arthritis. (31st January 2014) - Zimmermann, B; Köppert, S; Lefèvre, S; Rehart, S; Müller-Ladner, U; Neumann, E
Abstract : Background: Synovial fibroblasts (SF) play a central role in cartilage destruction and angiogenesis in rheumatoid arthritis (RA). RASF can migrate from their implantation site through the vasculature to distant implanted cartilage in the SCID mouse model. Interaction of RASF with endothelial cells (EC) is required for RASF-mediated angiogenesis and migration. In this study, expression of the E-selectin ligand CD15s, interaction of RASF with EC via E-selectin as well as kinetics of vascular growth induced by RASF in the SCID mouse model were analysed. Methods: Double staining in RA and osteoarthritis (OA) synovium for CD15s and vimentin as well as single staining for CD15s on serum stimulated RA- and OASF was performed. Flow assays were performed with RA- and OASF to analyse adhesion to selectin-coated capillaries as well as TNF-stimulated or latent HUVEC. In the SCID mouse model 1.5x10 5 RASF and healthy cartilage were implanted ipsilaterally and cartilage without RASF contralaterally. Implant images were taken, implants removed and angiogenesis analysed by CD31 staining. Neovascularisation next to and into the implants was determined at days 3-40. Results: All RA tissues (n = 12) expressed CD15s. Of those, in 67% CD15s signals were co-localised with vimentin, mainly in the sublining (50%) but also inside vessels (33%). In addition solely RA serum increased CD15s expression in RASF (80%, n = 5) and 33% of OASF (n = 3). RASF (n = 6) adhered significantly stronger to E-selectin-coated capillaries than to P-selectin at all flow rates (e.g. 18.4 ml/h: E-sel. = 16.6 ± 4.4 vs. P-sel. = 1.0 ± 1.5, p = 0.00001; 30.5 ml/h: E-sel. = 8.0 ± 3.5 vs. P-sel. = 0.2 ± 0.4, p = 0.0003). RASF adhered also significantly stronger to E-selectin coating than OASF (n = 5; e.g. 30.5 ml/h: E-sel. = 0.9 ± 0.3, p = 0.0016). Adhesion of RASF (n = 3) to TNF-stimulated HUVEC was significantly increased compared to OASF at 18.4 ml/h (9.7 ± 2.2). Anti-CD31 implant staining revealed that angiogenesis started at day 9, increased over time and was similar at both sites. Tortuous and larger vessels in the murine skin close to implants were visible early (day 3-12) and decreased over time, especially ipsilaterally. Later, during neovascularisation (day 9-40), small vessels sprouted into the implant. Conclusion: The data show that, RASF can express CD15s, the ligand for E-selectin and adhere stronger to E-selectin and to TNF-stimulated EC compared to OASF. In vivo, in the SCID mouse implants, RASF can actively induce neovascularisation illustrated by a distinct pattern in vessel formation. Thus, expression of CD15s and the ability to interact with EC could represent important steps for vascular transmigration relevant for RASF long distance migration.